Antibacterial activity of nisin, oregano essential oil, EDTA, and their combination against Salmonella Enteritidis for application in mayonnaise - Janine Passos Lima da Silva; Erika Fraga de Souza; Regina Celia Della Modesta; Izabela Alves Gomes; Otniel Freitas-Silva; Bernadette Dora Gombossy de Melo Franco (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
Salmonella Enteritidis (SE) is one of the most important serovars associated with Salmonella gastroenteritis outbreaks in Brazil. The use of natural antimicrobials can be an alternative method of SE control. The antimicrobial effect of two oregano essential oils (OEO1 and OEO2) at 0.1%, 0.2%, 0.5%, 1.0%, or 2.0%; nisin (Nisaplin®) at 0, 6.25, 12.5, or 25 ppm; ethylenediaminetetraacetic acid (EDTA) at 0.0037%, 0.0056%, 0.0075%, 0.0110%, or 0.0150%; and their combination against SE in vitro was studied to be applied in mayonnaise and Russian salad made with the same mayonnaise during storage at 8º or 30ºC for 24 hours. OEO was very efficient against SE at all tested concentrations, while nisin and EDTA showed no effect against SE. Ten volatile components were identified in the two OEOs using gas chromatography coupled to mass spectrometry with electron impact ionization, with carvacrol being the major component of both samples. OEO2, containing p-cymene (15.95%) and y-terpinene (6.90%), besides carvacrol (61.66%), resulted in larger inhibition zone than the other OEO (OEO1 don't contains p-cymene or  y-terpinene). Nisin in combination with OEO1 or OEO2 had an antagonistic effect at all concentrations. The presence of nisin caused a reduction in essential oil antimicrobial activity (p≤0.05). Sensory evaluation showed that consumers prefer 0.2% OEO in mayonnaise instead of 0.5% and 1.0% concentrations. Thus, OEO only, at a concentration of 0.2%, was applied in mayonnaise against SE. The Russian salad prepared with mayonnaise plus OEO at 0.2% (wt/wt) caused a reduction of SE when compared with the salad prepared with mayonnaise without OEO. These results indicate that the use of OEO as a biopreservative (natural antimicrobial) can enhance food safety, serving as an additional barrier in helping the Good Manufacturing Practices and the Hazard Analysis Critical Control Point program, fundamental to food safety.